Flipsnack-assisted IPAS E-Modules: Substance Forms and Changes for Student Engagement - Novi Wulandari; Zulherman (Postgraduate, University of Mataram, 2024)
Fun learning in the classroom is the use of interactive and innovative media because the use of media can make student active. But in reality, there are many factors that cause students to be inactive in the classroom, one of which is the use of media that in still not interesting. This creation of thi flipsnack-assisted E-module development aims to increase student activeness. The method used is Research and Development (R&D) the model used is the ADDIE model. This research was conducted in two schools, namely SDN Kapuk 02 Pagi & SDN Cijantung 03 Pagi. With research subjects of 120 grade IV students using control class and experimental class. Direct observation and testing were the methods used for data collection. In this study, researchers conducted validation, the validation carried out was validation of language, material, and media. Media expert validation results were 92% categorized as